Intracranial Undifferentiated Sarcoma Arising from a Low-Grade Glioma: A Case Report and Literature Review - Kim, Bum-Joon; Kim, Jong-Hyun; Chung, Hung-Seob; Kwon, Taek-Hyun (Journal of Korean Neurosurgical Society, 2015)
Undifferentiated sarcomas are rarely identified in the intracranial region. A 23-year-old man was admitted with a chief complaint of headache. Initial magnetic resonance images showed signs of low-grade glioma in the frontal lobe. Stereotactic biopsy was performed, and a diagnosis of diffuse astrocytoma was confirmed. Three months later, the patient presented with a high-grade tumor as seen on imaging studies. He underwent total resection of the tumor and histopathological tests identified an undifferentiated sarcoma. The patient died eight months later due to massive tumor bleeding. To the best of our knowledge, this is the first report of undifferentiated sarcoma arising from low-grade glioma without any chemotherapy or radiotherapy.